Physiological And Phytochemical Responses Of Baby Spinach (Spinacia Oleracea L.) Cultivars To Combined Npks Nutrition And Bacillus Subtilis BD233 Inoculation Using LC-MS - Theka - Kutumela, M.P.; Kanu, S.A.; Araya, H.T.; Sedibe, M.M.; Mudau, F.N. (Applied Ecology And Environmental Research 18(2):2129-2140., 2020)
Baby spinach (Spinacia oleracea L.) is grown for its nutritional benefits, edible leaves and medicinal purpose. The use of crop amendments such as inoculation with plant growth-promoting bacteria (PGPB) together with fertilizers for crop cultivation is more sustainable as it reduces the excessive use of fertilizers and increases crop yield. The aim of this study was to evaluate the physiological and phytochemical response of baby spinach cultivars to different levels of Nitrogen, Phosphorus, Potassium and Sulphur (NPKS) nutrition, amended with Bacillus subtilis strain BD233 inoculation. A factorial field experiment with treatments arranged in a randomized complete block design (RCBD) was carried out. The results showed that NPKS fertilization significantly affected the total biomass of baby spinach but not B. subtilis (BD233) inoculation and cultivar or their interaction. The level of chlorophyll varied between cultivars ranging from 19.96±1.62b mg/m2 and 24.79±1.98a mg/m2, however, no significant differences occurred in stomatal conductance among the three cultivars. However, significant difference was observed on compounds among cultivars with NPKS fertilizer application in most identified compounds such as patuletin-3-glucosyl-(1-6)[apiosyl(1-2)]-glucoside, spinacetin-3-glucosyl-(1-6)[apiosyl(1-2)]-glucoside, (S)-Malate and N-Acetyl-D-tryptophan. Therefore, the study recommends that fertilizer at 22N:22P:30K:5S kg/ha and 33N:33P:45K:7S kg/ha amended with B. subtilis inoculation be considered when cultivating baby spinach.
Article
Keywords: Chlorophyll content; Green leafy vegetables; Multivariate analysis; Plant Growth Promoting Bacteria (PGPB); Stomatal conductance